Combinatrial treatment of anti-High Mobility Group Box-1 monoclonal antibody and epothilone B improves functional recovery after spinal cord contusion injury. (November 2021) - Zhu, Yicheng; Uezono, Naohiro; Yasui, Tetsuro; Nakajo, Masahide; Nagai, Tatsuya; Wang, Dengli; Nishibori, Masahiro; Nakashima, Kinichi
Highlights: Combinatorial treatment with anti-HMGB1 mAb and Epo B improves locomotion recovery after spinal cord injury. Epo B facilitates axon outgrowth only in combination with anti-HMGB1 mAb. Intraspinal neurons play a critical role in the combinatorial treatment. Our findings provide a new strategy for SCI treatment without cell transplantation. Abstract: Spinal cord injury (SCI) causes motor and sensory deficits and is currently considered an incurable disease. We have previously reported that administration of anti-High Mobility Group Box-1 monoclonal antibody (anti-HMGB1 mAb) preserved lesion area and improved locomotion recovery in mouse model of SCI. In order to further enhance the recovery, we here examined combinatorial treatment of anti-HMGB1 mAb and epothilone B (Epo B), which has been reported to promote axon regeneration. This combinatorial treatment significantly increased hindlimb movement compared with anti-HMGB1 mAb alone, although Epo B alone failed to increase functional recovery. These results are in agreement with that anti-HMGB1 mAb alone was able to decrease the lesion area spreading and increase the surviving neuron numbers around the lesion, whereas Epo B facilitated axon outgrowth only in combination with anti-HMGB1 mAb, suggesting that anti-HMGB1 mAb-dependent tissue preservation is necessary for Epo B to exhibit its therapeutic effect. Taken together, the combinatorial treatment can be considered as a novel and clinically applicable strategy for SCI.